Singing the French Revolution : Popular Culture and Politics, 1787-1799 - Mason, Laura (Book collections on Project MUSE., 1996)
Laura Mason examines the shifting fortunes of singing as a political gesture to highlight the importance of popular culture to revolutionary politics. Arguing that scholars have overstated the uniformity of revolutionary political culture, Mason uses songwriting and singing practices to reveal its diverse nature. Song performances in the streets, theaters, and clubs of Paris showed how popular culture was invested with new political meaning after 1789, becoming one of the most important means for engaging in revolutionary debate.